2007
DOI: 10.1038/sj.bmt.1705950
|View full text |Cite
|
Sign up to set email alerts
|

Aging of registered stem cell donors: implications for donor recruitment

Abstract: With more than 11 million registered stem cell donors worldwide and limited resources for health systems, it seems questionable if investments in ongoing donor recruitment are useful. Since there is evidence that transplant outcomes are better with younger donors, the age distribution of registered donors is highly relevant in this context. One might argue that the usefulness of a donor file decreases if there is no new donor recruitment not only as a result of loss of donors who reach the age limit for donati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Figure 4. The curve for German donors differs considerably from an earlier published version for the total DKMS file 10 for two reasons in the main. First, there was ongoing donor recruitment with a specific focus on young donors between these two snapshots.…”
Section: Potentially Accessible Minority Donorsmentioning
confidence: 46%
See 1 more Smart Citation
“…Figure 4. The curve for German donors differs considerably from an earlier published version for the total DKMS file 10 for two reasons in the main. First, there was ongoing donor recruitment with a specific focus on young donors between these two snapshots.…”
Section: Potentially Accessible Minority Donorsmentioning
confidence: 46%
“…However, an exhaustive quantitative cost-benefit analysis of donor recruitment has not yet been accomplished for several reasons. 4,10 The closely related question of optimal donor registry size is therefore still unresolved. Apart from these general difficulties, there are additional problems in our minority program setting that have to be taken into account when analyzing the program benefits: First, it is difficult to assess to which extent patients in Turkey benefit from ongoing donor recruitment, as the EBMT activity survey suggests that non-HLA barriers to transplantation play an important role for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, more than 6,000,000 additional donors are necessary to reach the same matching probability in Scenario A that describes the current matching standard of high-resolution matching for the HLA-A, HLA-B, HLA-C, and HLA-DRB1 genes as in Scenario D. On the other hand, such huge numbers indicate how difficult it is to substantially improve patients' chances of finding optimal matches. Although ongoing donor recruitment seems essential to compensate for aging of registered donors [27], there is also a need for innovative recruitment strategies that efficiently increase the number of available HLA phenotypes [28].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the USA and Hong Kong studies indicated that younger people were more willing to donate [14,17]. Meanwhile, a study in Germany found that newly recruited donors were between the ages of 34.0 and 39.7 years old [21,23]. This might be because younger people -especially new generations -have access to the internet and social media and can easily obtain information and become enlightened about new treatment strategies such as hematopoietic stem cell transplantation.…”
Section: Vmentioning
confidence: 98%